Innovation capacity in urban agglomerations: The role of digital finance - Kai Tang; Xiaopei Cai; Haijie Wang (Journal of Innovation & Knowledge (JIK), 2025)
Using panel data of 196 cities in 19 urban agglomerations in China from 2012 to 2021, this study analyzes the impact of digital finance on the innovation capacity of urban agglomerations and the underlying mechanisms. The level of digital finance development is measured using Peking University's Digital Financial Inclusion Index. Meanwhile, by manually sorting the relevant evaluation indicators in CSSCI journal papers, creating frequency statistics, and combining the total and average indices, innovation capacity is measured from five aspects: innovation resources, knowledge creation, innovation performance, innovation environment, and innovation collaboration. The results show that digital finance promotes the innovation capacity of urban agglomerations. This effect is stronger for small-scale, highly marketized, and polycentric urban agglomerations. Mechanism analysis shows that, first, via the agglomeration of innovation capital, digital finance provides financial support for improving the innovation capacity of urban agglomerations. Second, by improving entrepreneurial activity, digital finance promotes the formation of an innovation ecosystem. Third, by enhancing credit resource allocation, digital finance encourages more innovation funds to flow into innovative enterprises and promotes innovation capacity in urban agglomerations. Finally, economic policy uncertainty plays an 'inverted N-type,' nonlinear moderating role in the relationship between digital finance and innovation capacity. In summary, by introducing digital finance as a key variable into urban agglomeration innovation research, this study expands the theory of financial and regional innovation systems. Next, demonstrating the heterogeneous impact of digital finance on different types of urban agglomerations, the findings can serve as a benchmark against which urban agglomerations can be compared to develop differentiated digital finance development strategies. Finally, the insights can inspire managers to re-examine the complex influence of economic policy uncertainty in the innovation process, which may help them make sound economic decisions.
Keywords: O11; R10; G10; 650; Urban agglomeration; Innovation capacity; Digital finance; Mediating effect; Economic policy uncertainty